CHANGES IN FOOD CONSUMPTION PATTERNS AMONG THE HAJONGS COMMUNITY IN THE CHANGLANG DISTRICT OF ARUNACHAL PRADESH - Deori, Niranjan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Preferences and availability are closely linked to different community food cultures and choices. This study aims to investigate the food consumption habits of the Hajongs community in the Changlang District of, Arunachal Pradesh. A total of 200 adult Hajong members were selected, and their food intake patterns were analysed using a semi-structured food frequency questionnaire. Rice emerged as the staple cereal for all Hajongs, while wheat was consumed two to three times in monthly. Pulses are negligible consume in their diet because mostly they depends on green leafy vegetables. Green leafy vegetables including Malabar spinach, creeping wood sorrel, palak, and cabbage etc. were commonly consumed twice a week by the Hajong peoples in the study area. Vegetables like cauliflower, ladies finger, cluster beans, cucumber, various gourds, brinjal, and drumstick were consumed twice or thrice weekly depending on availability. Approximately 49.5% of the Hajongs population consumed tapioca, yam, and sweet potato twice weekly, subject to availability. Ginger is used by a majority (97.5%) of the selected Hajong individuals. Fruits such as banana, guava, and papaya were regularly part of their diet. Around 60% milk consuming daily. Mustard oil was the primary and widely used cooking oil in the Hajong community in the study area. Eggs, fish, crab, poultry, and mutton were preferred by 40% on an average of the Hajong populations, typically on an occasional basis, while the remaining 60% did not consume these items as they were not staple foods. Around 70% consumed biscuits daily, and 5% consumed fast foods such as Maggie, Chowmein, Thukpha (Chinese dish) popular in the study area, and chat items once a month. Nearly 1% preferred purchasing instant food products such as, masala powders, and pickles etc. Only one percent reported eating outside food once or twice a week, usually when they away from their resident for occupational reasons. This study highlights an ongoing nutritional transition characterized by a shift from nutrient-rich traditional diets to energy-dense market foods, a trend observed not only among the Hajongs community but also across indigenous populations in India and worldwide.